Ecology and comparativism: planetary space between dwelling and displacement in contemporary French and English poetics - La Vedrine, Sam (2019)
This thesis looks at the poetry and conceptual apparatus of four poets working in French and English during the past several decades who develop distinct poetic epistemes following precepts of natural and cultural ecology and comparativism. It questions how their poetics merges the comparative practice of analogy with ecological discourse to highlight an intersection of the politics and aesthetics of a planetary space under threat, simultaneously, from destructive treatment of the Earth and globalisation’s exclusive representations and effacements of difference.